Transcriptional alteration of NF-κB-associated long noncoding RNAs in the stomach of Helicobacter pylori-infected and non-infected patients - Marzieh Ghanbarian; Ronak Bakhtiari; Seyedeh Zohre Mirbagheri; Fatemeh Rezaei; Abbas Rahimi Foroushani; Masoud Alebouyeh (Journal of Infection in Developing Countries)
Introduction: Helicobacter pylori could colonize the gastric mucosa and cause gastritis, ulcers and cancer. Numerous virulence factors have been identified in this bacterium that play important roles in promoting gastric disorders. Although the interaction of long noncoding RNAs (lncRNAs) with transcription, processing, and translation of genes associated with different diseases are described, their interaction with the inflammatory genes and H. pylori infection in the gastric tissue is not well known. This study compared changes in common NF-κB-regulatory lncRNAs in the gastric tissue of H. pylori-infected and non-infected patients with gastritis. Moreover, a link between the virulence entity of the strains and the transcriptional changes was analyzed.